STRATEGI MENAGGULANGI ALIH FUNGSI LAHAN DAN DAMPAKNYA DI KECAMATAN SABAK AUH KABUPATEN SIAK - Muhammad David Hermanda; Eri Sayamar; Kausar Kausar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of this study is: 1) Identify factors causing land convertion in the Subdistrict Sabak Auh District Siak. 2) Know coping strategies land convertion rice plants in the Subdistrict Sabak Auh District Siak. This research held in the Sub District Sabak Auh District Siak. The method in this research is : survey method. Sampling technique is purposive sampling. 30 farmers are doing land convertion from plants rice to oil palm plantations taken as respondents. Analysis of data to answer the goal that is using likert scale. To answer the second goal using SWOT analysis. The result showed: 1) There are four aspects of the cause of land convertion. economi aspect ‘Agree’, environmental aspect ‘Quite Agree’, technical aspects ‘Quite Agree’, social aspects ‘Quite Agree’. Causing farmers to land convertion from rice plants to palm oil plntations caused by economic aspects. 2) there are three strategies to overcome land convertion that is : a) With adequate irrigation system, optimal extention role, made laws about land convertion can compete with palm oil plantations income side, b) rice plants is the highest demand and easy marketing that can meet the needs of the community. c) with strict legislation will lead to the need for rice is met.Keywords :Land Convertion, Tackle Land Convertion, Rice Plants, Oil Palm Plantation